2016
DOI: 10.3892/etm.2016.3677
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cell transplantation combined with erythropoietin for the treatment of spinal cord injury in rats

Abstract: Abstract. Spinal cord injury (SCI) comprises nerve and motor function disorders that may be caused by a variety of damaging factors and is challenging to treat. The aim of the present study was to investigate the regenerative effects of neural stem cell (NSC) transplantation combined with intraperitoneal injection of erythropoietin (EPO) on cross-sectional SCI in rats. A model of SCI was induced in 40 adult Wistar rats via the complete transection of the 10th thoracic vertebra (T10). The rats were allocated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…In our T10 transection SCI rats, the BBB scores for the control group stayed at 0 from the surgery to the end of the first week after surgery. They then increased gradually after week 2 after surgery and reached 1/3 of the score of the sham group at the end of week 12, which showed a similar hindlimb movement recovery pattern with a same recovery start time and a similar level of maximum recovery, but a slower recovery rate as observed in other studies about T10 SCI transection rat models . The obvious lusterless surface, big embossed intumescent scar, and big holes in the transection region of the injured spinal cords in our study were consistent with observations in previous studies …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our T10 transection SCI rats, the BBB scores for the control group stayed at 0 from the surgery to the end of the first week after surgery. They then increased gradually after week 2 after surgery and reached 1/3 of the score of the sham group at the end of week 12, which showed a similar hindlimb movement recovery pattern with a same recovery start time and a similar level of maximum recovery, but a slower recovery rate as observed in other studies about T10 SCI transection rat models . The obvious lusterless surface, big embossed intumescent scar, and big holes in the transection region of the injured spinal cords in our study were consistent with observations in previous studies …”
Section: Discussionsupporting
confidence: 92%
“…Since, there was a close correlation between the number of NF200‐positive neurons/the degree of neuronal cell body staining and lower limb functional recovery following SCI, NF‐200 staining has been used as a marker for nerve regeneration . The low expression of GAP‐43 and NF‐200 in the transection region of the spinal cords of the control rats, which was also observed by Zhao et al suggested that the growth of the axons and sprouting of the nerves had almost stopped at week 12 after surgery.…”
Section: Discussionmentioning
confidence: 72%
“…In our study, we identified Que increased 5‐HT‐positive nerve fibres after SCI. NF‐200 is a neurofilament protein that constitutes the framework of nerve axons 26 . NeuN serves as neuronal marker in several pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Papers published outside the 10-year time period from 2012 to 2022 were excluded, papers assessing treatments for other central nervous system injuries other than SCI were also excluded, and papers attempting to enhance delivery of a previous known treatment or attempting to replicate the results of a previous treatment were also excluded, leaving 130 articles that required a full text read to assess for eligibility. Following full text reads of these articles, the final selection of 44 studies were identified and included for analysis in this systematic review [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The literature search process and screening for eligibility is presented in the PRISMA diagram below ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%